THE DEVELOPMENT OF HOUSING AND IT’S SOCIO-ECONOMIC IMPACTS TO THE LOCAL COMMUNITY Case Study: Semarang Sub Urban, Dictrict Tembalang - Rahman, Arief (Universitas Gunadarma, 2014)
The development of suburban areas indicate that the area to be “exurban area”, that the development of the new urban population in large numbers came from the city and moved because it was attracted by the new residence or employment opportunities, but in socio-economic them still remain oriented to the city core. Another phenomenon of the development of the suburb that is the restructuring of the city’s core as result of the shift of functions from manufacturing center to the center of financial activities and services, while manufacturing activity increasingly shifts to the edge of the area, especially with the development of insdustrial areas and other. As for the purpose ofof this research is to know the socio-economic impacts of development of Semarang’s suburban housing, District Tembalang to the local community. A method of research used in this research is approach case study using by data qualitative and quantitative furnished with. The main data used is the quantitative data obtained from the questionnaire. A case study is a research that analys in one case and conducted in intensively, deep, specifics and comprehensive. This research is still with a limited number of respondendts and expected there is the research continued with more sample so the data more be valid. The socio-economic impacts of housing has already been seen in the public therefore particularly the government to immediately solve the problems of this mismatch so as not to be increased. Keywords: regional development, housing development, socio-economic effects